An interpersonal skills workshop for preparing special education teachers - Gerber, S.A.; Drezek, S. (Education and the Training of the Mentally Retarded, 1977)
The findings in this study that self reported acceptance of self and others and interpersonal skills increased following the Workshop must themselves be regarded within the limitations of a small sample, an analysis of only one leader's group participants, measurements by ratings, and a quasi experimental design. Nevertheless, human relations training appears to be a valuable component to program more systematically into teacher education. Work in developing specific training goals and procedures relevant to personal growth as related to competence in the classroom is the next step. The fact that such a short training program could affect the way student teachers feel about themselves should encourage further research and experimentation.
Keywords: dept.sed; mental deficiency; methodology; normal human; psychodrama; teacher; theoretical study; training; vocational education; ⛔ No DOI found